DO ISO14001 EMS COMPANIES IN MALAYSIA REWARD EMPLOYEES FOR ENVIRONMENTAL INITIATIVES? - KAUR, Harjeet (Journal of Environmental Management and Tourism, 2016)
The environmental management literature recommends that companies committed towards achieving their sustainable environmental aspirations should establish a rewards scheme for reinforcing employee motivation in the search for innovative solutions to environmental problems. This paper will assess whether rewards1 will provide a good indicator of employee willingness to try eco-initiatives2 in some of the leading environmentally proactive ISO 14001 companies in Malaysia. Of the two hundred and twenty three survey responses used in the final data analysis, two hundred and eleven responses are from the recipients of the Malaysian Prime Minister’s Hibiscus Award (PMHA). The PMHA was first launched in 1996 as Malaysia’s premier private sector environmental award for business and industry. Moreover given that employees’ job appraisals rarely include an environmental category, several environmental initiatives are proposed which could provide practitioners a tool to assess employees’ performance evaluation. The data was treated to descriptive, reliability, validity and correlation analysis using the SPSS computer program version 16. The rewards and employee willingness to try eco-initiatives constructs exhibited good internal consistency and adequate construct validity. In summary the findings suggest that middle and lower level employees are rarely rewarded for their environmental initiatives.